Taking stock of the field of populism research: Are ideational approaches `moralistic' and post-foundational discursive approaches `normative'? - Seongcheol Kim (Politics, 2022)
This article sets out to examine two claims that have increasingly come to define the dividing lines between the ideational and the post-foundational discursive approaches to populism: namely, that the former is moralistic and the latter is normative in orientation. The article considers the conceptual merits of both critiques while using them to further examine some of the implicit assumptions and pitfalls within Cas Mudde's and Ernesto Laclau's paradigmatic conceptualizations of populism. It is argued that ideational scholars' attribution of a moralistic particularity to populism runs the risk of pathologizing the latter for characteristics that are arguably constitutive of all politics, while the danger of a certain crypto-normativity can be seen in Laclau's tendency to equate populism with the political and simultaneously emphasize its emancipatory effects. The key difference between the two approaches ultimately consists in the location that they assign to populism within the wider topography of politics itself.
Keywords: 300; Cas Mudde; discourse; Ernesto Laclau; ideology; populism